Report of a novel mutation in the slc26a2 gene foud in a colomian adult patient with diastrophic dysplasia (2013)
Background. Diastrophic dysplasia is an osteochondrodysplasia belonging to the group of dysplasias caused by mutations in the diastrophic dysplasia sulfate transporter. This sindrome is a micromelic dysplasia with multiple bone deformities of the hands, feet, knees and spine.Objective. Describe the first report of diastrophic displasia in Colombia Materials and methods. In this paper a Colombian adult patient with diastrophic dysplasia whose clinical diagnosis was confirmed at the molecular level is reported.Results. In this first report of diastrophic dysplasia in Colombia we found that the patient was compound heterozygote for the already reported Arg279Trp substitution and an unpublished mutation, a Ser157Thr substitution in the SLC26A2 gene.Conclusion. Bioinformatic analysis on the latter mutation suggested that it could correspond to a deleterious mutation because it is in a highly conserved domain of the sulfate transporter